Images of Russians in the Japanese pop culture (on the example of anime) - Gronowska, Weronika (Vilnius University Open Series, 2024)
The article seeks to identify and analyse the ways of depicting Russians in the contemporary Japanese pop cultural texts. The following anime series were chosen as the object of the study: Black Lagoon; Darker than Black: Gemini of the Meteor; Hetalia Axis Powers; Bungou Stray Dogs; Yuri!!! on Ice; How Heavy are The Dumbbells You Lift?. The author of the article considers different stereotypes related to Russia and its inhabitants, and also covers such issues as age and gender, appearance and language, lifestyle and character traits of the Russian characters.